FACTORS INFLUENCING BANKS CAPITAL ADEQUACY RATIO IN INDONESIAN BANKS: CASE STUDY AT COMMERCIAL BANK LISTED PERIOD 2010-2015 - Runtu, Franklin .; Saerang, David .; Pangemanan, Sifrid . (FEB Universitas Sam Ratulangi Manado, 2017)
Abstract: Banks play a major role in foresting the economy of a nation. It serves as an intermediary for people with excess of money to the people in need of money. In carrying out its function, banks must maintain the capital adequacy that is used to assess its ability to bear risk that might occur. This research focuses on examining the factors that influence Indonesian commercial banks capital adequacy ratio (CAR). Fixed effect with least square dummy variable and 61 commercial banks as sample is used in the research. The result shows that operating expense to operating income ratio and total asset has a positive and significant influence to CAR. NIM is shows positive relationship with CAR this variable is found to be statistically significant. High level of capital will increase cash reserves that can be used to extend credit and high solvency level will open greater opportunities for the bank to improve its profitability. Conversely, low solvency level will reduce the bank?s ability to improve profitability, reduce public trust and affect its continuity.Keywords: capital adequacy ratio (Car), net interest margin (nim), operating expense to operating income ratio (oeoi), total asset